Pengaruh Manajemen Pembelajaran Problem Based Learning (PBL) dan Minat Belajar terhadap Prestasi Siswa SD - Ratu Anggraini; Siswoyo; M. Badrun (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the influence of Learning Management based on Problem Based Learning(PBL) and Learning Interest on Student Achievement in State Elementary Schools in Pugung District.The PBL model is considered effective in improving students’ critical thinking and problem-solvingskills. The research method used was quantitative with an ex post facto approach, involving 100teachers from 36 schools in the sub-district. Data was collected through questionnaires and conceptcomprehension tests, then analyzed using multiple linear regression. The results showed that PBLLearning Management had a significant positive influence on student achievement, with a regressioncoefficient of 0.571. In addition, Interest in Learning also contributes positively to student achievement,with a regression coefficient of 0.593. Simultaneous tests showed that the two variables togetherexplained 70.7% of the variation in student achievement. These findings confirm the importance ofgood learning management and the development of learning interests in improving student learningoutcomes. This research is expected to be the basis for the development of more effective educationpolicies in rural areas.